Virtual Tour Actual Usage: The Influence of Perceived Benefits and Sacrifices - Azzahra Putri Ramadhanty; Putu Wuri Handayani; Ave Adriana Pinem; Muhammad Hafizhuddin Hilman (Jurnal Sistem Informasi, 2021)
Virtual tours are developed as alternatives to traditional tourism in Indonesia. This quantitative study analyzed factors that influence actual virtual tour usage. A survey was conducted with 1,125 respondents who were aware of virtual tour services. The data were processed using covariance-based structural equation modeling. The results indicate that perceived benefits and sacrifices influenced behavioral intention to use these services. However, accessibility did not affect this intention. Behavioral intention to use significantly affected actual virtual tour usage. This research can help virtual tour providers and regulators increase service utilization and implementation.